Relación entre el marketing interno y el compromiso organizacional en el call center IBR Perú 2018 - Palomino Meneses, David (2018)
The main objective of the research work was to determine if there is a relationship between internal marketing and the organizational commitment of the IBR Peru Call Center operators in the year 2018. The research design is non-experimental of cross section because the variable of study will not be manipulated and the level of study is descriptive correlational. The survey was measured with the Likert scale and was applied to 100 workers of the company Call Center IBR Peru. This study concluded that the development of employees has been partially because the company does not comply with the established promises since, it did not give the complete information to be able to obtain the benefits or incentives for the fulfillment of goals, likewise, the personnel considers important the trainings established by the company but not in the majority are talks and not certified training, with the trainers being the most experienced personnel.